Oesophageal and gastric intestinal-type adenocarcinomas show the same male predominance due to a 17 year delayed development in females. Issue 1 (6th October 2008) - Derakhshan, M H; Liptrot, S; Paul, J; Brown, I L; Morrison, D; McColl, K E L
Abstract : Background and aims: Upper gastrointestinal adenocarcinomas show an unexplained male predominance that is more apparent in oesophagus than stomach and in intestinal than diffuse histological subtype. We have conducted a population-based study to determine whether the gender phenomenon is primarily related to the anatomical site or the histological subtype. Method and materials: Of 3270 gastric and oesophageal cancers recorded in the West of Scotland Cancer Registry, 1998–2002, 812 were randomly selected for detailed analysis. The Lauren histological subtype of adenocarcinoma was determined by reviewing 1204 original reports and 3241 biopsies. Results: Analysis included 405 non-cardia cancers, 173 cardia cancers and 209 oesophageal adenocarcinomas. Crude incidence rate of intestinal subtype was higher in males (23.86/100 000 person-years) versus females (9.00/100 000 person-years), giving a male/female (M/F) ratio of 2.65 whereas diffuse subtype was similar for both genders (5.58 vs 5.20/100 000 person-years) yielding M/F of 1.07. The M/F ratios for oesophageal, cardia and non-cardia gastric cancer were 3.5, 2.0 and 1.6, respectively. Multiple logistic regression indicated that the odds of male gender was related to the histological subtype rather than anatomical location (odds ratio 2.6, 95% confidence interval 1.78 to 3.9). Curve fitting of the age-specific incidence of intestinal subtype indicated that similar functions describe the rise in incidence with age in males and in females. However, the age-specific incidence of female intestinal subtype was delayed by 17.3 years. The M/F ratio of intestinal subtype was 3.41 at age <50 years, peaked at 7.86 at age 50–59 years and then showed a progressive decrease after 50–60 years of age. Conclusion: Male predominance of upper gastrointestinal adenocarcinoma is related to the intestinal histological subtype rather than tumour location and is due to marked delayed development of this subtype in females prior to 50–60 years of age.